Regulasi dan Sistem Pembayaran Digital Syariah - Riani Riani; Refadiani Refadiani; Clara Rahma Ayunda Isnaini; Muhammad Zaki; Mabruri Mabruri (Jurnal Global Futuristik, 2026)
The development of fintech and digital payments in Indonesia has created challenges regarding sharia compliance, while specific regulations remain limited, resulting in a regulatory gap. This study aims to analyze the regulation of sharia digital payment systems in sharia economic law, identify regulatory gaps, and formulate the integration of sharia principles into technical mechanisms. The method used is normative juridical with a descriptive qualitative approach through literature review, analyzing laws and regulations, DSN-MUI fatwas, and related literature. The results show that legal frameworks such as the Sharia Banking Law, PBI, and DSN-MUI Fatwas already exist, but specific regulations are limited. The main regulatory gaps include the absence of contract provisions in automated transactions (algorithms and smart contracts), real-time sharia supervision, and sanction procedures for violations of sharia principles. Sharia principles (justice, transparency, prohibition of riba, gharar, maysir) can be integrated through sharia compliance, DSN-MUI certification, Sharia Supervisory Board, and contracts such as wadiah, qardh, ujrah, murabahah, hawalah, sharf. This study recommends harmonization of regulations between authorities (BI, OJK, DSN-MUI), improvement of sharia financial literacy, equitable distribution of digital infrastructure, and strengthening the role of technology-based DPS so that sharia digital payment systems can develop inclusively and fairly.